2009
DOI: 10.1055/s-0029-120722
|View full text |Cite
|
Sign up to set email alerts
|

Present Risk of Anthracycline or Radiation-induced Cardiac Sequelae Following Therapy of Malignancies in Children and Adolescents

Abstract: Anthracyclines are very potent drugs in the therapy of malignancies in childhood. The major dose limiting adverse effect of these drugs is the risk of dilated cardiomyopathy. We performed a retrospective study on 168 patients who were treated with anthracyclines for a malignant disease with or without chest radiation at the department of Pediatric Hematology and Oncology at the University of Duesseldorf between 2000 and 2004. During and after chemotherapy the patients were screened by echocardiography and ECG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…55,452,453 These changes have been found primarily in adults, with only a 2% incidence of supraventricular tachycardias reported in children during treatment with anthracyclines. 454 Only scattered reports address the issue of arrhythmias late after chemotherapy. A study of 11 children reported that anthracycline treatment may be a risk factor for torsade de pointes weeks or years after therapy for leukemia, and such cases are generally related to QT-prolonging agents or to hypokalemia.…”
Section: Screening For Arrhythmias and Conduction Defectsmentioning
confidence: 99%
“…55,452,453 These changes have been found primarily in adults, with only a 2% incidence of supraventricular tachycardias reported in children during treatment with anthracyclines. 454 Only scattered reports address the issue of arrhythmias late after chemotherapy. A study of 11 children reported that anthracycline treatment may be a risk factor for torsade de pointes weeks or years after therapy for leukemia, and such cases are generally related to QT-prolonging agents or to hypokalemia.…”
Section: Screening For Arrhythmias and Conduction Defectsmentioning
confidence: 99%
“…Furthermore, in order to prevent arrhythmias related to cancer treatment, Herman recommended identifying patients with ECG changes before treatment and eliminating other comorbidities that predispose these patients to arrhythmias. 21 Chen et al 22 retrospectively evaluated 168 patients treated for pediatric malignancy in terms of cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, chemotherapy drugs affect radiation-induced heart damage. For example, a previous study demonstrated that the use of anthracyclines increased radiation-induced cardiac toxicity (16). Another study indicated that when 240-300 mg/m 2 doxorubicin accumulated, cardiac dysfunction increased after postoperative radiotherapy (17).…”
Section: Discussionmentioning
confidence: 99%